(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the interpretation of the Amir Temur was analyzed in the era of independence. In particular, the image of the Amir Temur domain in the drama AdylYaubov “My Will to the Generations”, ability of the author to conjure the historical image.